Retrospective observational study and comparative review of lymph node yield in open vs. laparoscopic surgery for colorectal cancer - Elamin Elsadig Abdalla, MR. Ahmed (International Journal of Medicine, 2020)
Laparoscopic surgery is standard treatment for colorectal cancer in the last decade of surgery’s history. Nowadays  open surgery for CRC indicated only for certain cases. with evolving of laparoscopic instruments and adoption of laparoscopic and robotic techniques by new generation of surgeons open surgery started to vanish gradually as standard care in all world well equipped hospitals and centers . Short and long term advantages of laparoscopic approach manifested in it is minimum invasive technique and less sequelae of wound healing respectively, but in CRC surgical procedures staging and eradication of neoplasm have great impact in survival and morbidity outcome. This study compare laparoscopic with open surgical technique for CRC using lymph node yield as oncological determinant factor for prognosis and need for further treatment.